A panoramic review on ethnomedicinal, therapeutic, phytochemical, and advance attributes, of the genus Ziziphus Mill., native to Pakistan - Imran, Sehrish; Bibi, Yamin; Munawar, Tayyaba; Yousaf, Abdul Manan; Hasnain, Muhammad; Mashwani, Zia ur Rehman (Ethnobotany Research and Applications, 2023)
Background: Medicinal plants have gained prime importance in treating several fatal diseases, such as cancer, diabetes, and eczema, because they are a rich source of bioactive phytochemicals and a safer alternative to synthesized chemical compounds. Genus Ziziphus Mill. belongs to the family Rhamnaceae, which comprises 100 accepted plant species and is well known for multipurpose applications such as food, fodder, fuels, medicine, timber, alcohol, cosmetics, poison, etc. Six species of the genus Ziziphus are indigenous to Pakistan, famous as Ziziphus nummularia (Burm.f.) Wight & Arn., Ziziphus mauritiana Lam., Ziziphus jujuba Mill., Ziziphus spina-christi (L.) Desf., Ziziphus rugosa Lam., Ziziphus oxyphylla Edgew. Method: Several search engines and online databases, including Sci-hub, PubMed, Google Scholar, Flora of Pakistan, research gate, and Science Direct, were used to perform an exhaustive literature survey for this review. Both original research studies and relevant review articles done till 2022 were included. Result: These species have been used in traditional and Ayurveda medicine to treat diseases like fever, skin infections, urinary problems, diabetes, etc. Numerous components of Ziziphus species have been found, alkaloids, flavonoids, phenols, terpenoids, and organic acids, to exhibit a variety of biological properties, including anticancer, antimicrobial, anti-hair fall, antinociceptive, antipyretic, larvicidal, and anti-diabetic actions. Conclusion: This review demonstrates the phytochemical composition, traditional uses, pharmacological properties, and nanoparticle-based activity of the genus Ziziphus and lays down a scientific foundation for further investigation on the usage of Ziziphus. Moreover, this review indicates that jujube has a hair growth effect because of its high nutritional value and pharmacological activities. Keywords: Cancer; Ethnobotany; Nanoparticles; Pharmacology; Phytochemical; Ziziphus.